Resenha: BELO, Duarte. O núcleo da claridade: entre as palavras de Ruy Belo. Lisboa: Assírio & Alvim, 2011. 240 p. (Revista do Centro de Estudos Portugueses, 2013)
Resenha: BELO, Duarte. O núcleo da claridade: entre as palavras de Ruy Belo. Lisboa: Assírio & Alvim, 2011. 240 p.